Motivations and Limits for COVID-19 Policy Compliance in Germany and Switzerland - Bettina Zimmermann; Amelia Fiske; Stuart McLennan; Anna Sierawska; Nora Hangel; Alena Buyx (Kerman University of Medical Sciences, 2022)
Background  In contrast to neighboring countries, German and Swiss authorities refrained from general curfews during the first pandemic wave in spring 2020, calling for solidarity and personal responsibility instead. Using a qualitative methodology, this study aims to explore why people in Germany and Switzerland were motivated to comply with policy measures during the first wave of the coronavirus disease 2019 (COVID-19) pandemic, and what factors hindered or limited their motivation. While quantitative surveys can measure the level of compliance, or broadly ask what motives people had for compliance, we here strive to explain why and how these motives lead to compliance.  Methods  This publication has been made possible by the joint work of the members of the "Solidarity in times of pandemics" (SolPan) research commons. Seventy-seven semi- structured qualitative interviews were conducted with members of the general public in Germany (n = 46) and the German-speaking part of Switzerland (n = 31) in April 2020. Interviews were transcribed and analyzed following a grounded theory approach.  Results  Three themes were identified that summarize factors contributing to compliant or noncompliant behavior. (1) Social cohesion was, on the one hand, an important motivator for compliance, but at the same time related to conflicting needs, illustrating the limits of compliance. (2) Consequences were considered on both the individual level (eg, consequences of individual infection) and societal level (eg, the societal and economic consequences of restrictions). (3) While for some participants following the rules was perceived as a matter of principle, others stressed the importance of making their own risk assessment, which was often associated with with a need for evidence on the effectiveness and reasons behind measures. Conclusion  A variety of motives contribute to COVID-19 related compliance. Authorities should seek to address these multi-faceted aspects to support motivation for compliance in a large proportion of the population.